EXPLORING STUDENTS’ PERCEPTIONS OF BILINGUAL PROGRAM’S IMPACT ON ENGAGEMENT IN EFL CLASSROOM - Zulfah, Sabilla Aprilia; Novitasari, Heni (STKIP Siliwangi, 2025)
The increasing use of English as a global language over the past few decades has significantly increased its use worldwide, including in Indonesia. Despite its importance, limited research has focused on the role of bilingual education in enhancing student engagement in English as a Foreign Language (EFL) classroom. This study aims to explore students' perceptions regarding the impact of the bilingual education program on their cognitive, emotional, and behavioral engagement in English as a Foreign Language (EFL) class at Al Azhar 19 Cibubur Islamic Junior High School. The study employed a qualitative descriptive research approach. Data were collected using questionnaires, involving 60 students from bilingual classes as respondents. The data were then analyzed to determine the extent of engagement in three domains. The findings revealed that the bilingual education program positively influenced students' engagement, with 25% of respondents indicating strong cognitive engagement, 39% demonstrating emotional engagement, and 37% showing behavioral engagement. These results highlight the program's potential in fostering active participation and motivation in EFL learning environments.